2010
DOI: 10.1103/physrevb.81.060501
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric evidence of multiband superconductivity inBa(Fe0.925Co0.075)2

Abstract: We report on the determination of the electronic heat capacity of a slightly overdoped ͑x = 0.075͒ Ba͑Fe 1−x Co x ͒ 2 As 2 single crystal with a T c of 21.4 K. Our analysis of the temperature dependence of the superconducting-state specific heat provides strong evidence for a two-band s-wave order parameter with gap amplitudes 2⌬ 1 ͑0͒ / k B T c = 1.9 and 2⌬ 2 ͑0͒ / k B T c = 4.4.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 39 publications
13
115
1
Order By: Relevance
“…It is worth to mention that γ r in our SC samples reaches 12.6%, 3.8%, and 6.5% of the normal state Sommerfeld coefficient γ n for x = 0.092, 0.096, and 0.10, respectively. A similar observation of (γ r /γ n ≈ 5.7%-24%) [47,49] was also reported in iron pnictide superconductors.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…It is worth to mention that γ r in our SC samples reaches 12.6%, 3.8%, and 6.5% of the normal state Sommerfeld coefficient γ n for x = 0.092, 0.096, and 0.10, respectively. A similar observation of (γ r /γ n ≈ 5.7%-24%) [47,49] was also reported in iron pnictide superconductors.…”
Section: Resultssupporting
confidence: 62%
“…In addition, γ n increases with Ni doping, illustrating the competition between magnetism and superconductivity. We believe, however, that the presence of multiple SC gaps may reduce the universal parameter, as evidenced in other 122 Fe-based superconductors [47]. It has been also well reported that the reduced jump in the specific heat C p /T c compared to that of a single-band s-wave superconductor might be related to a pronounced multiband character with rather different partial densities of states and gap values [24].…”
Section: Resultsmentioning
confidence: 98%
“…Comparably small values of Δ 2 (0), as measured by α 2 , have been reported in electron-doped BaFe 2 As 2 -α 2 = 0.95 in Ref. 23 and α 2 = 0.957 in Ref. 24 -but, given the differences between the electron-and hole-doped compounds, the implications of this similarity in the values of α 2 are not clear.…”
Section: Discussionmentioning
confidence: 92%
“…To account this negligible variation, we use scaling coefficients close to unity. As an example, for Ba0.67K0.33Fe2As2 one may choose Ba(Fe0.847Co0.153)2As2 [46], Ba(Fe0.88Mn0.12)2As2 [47], BaFe1.75Ni0.25As2 [48].…”
Section: Specific Heat Measurementsmentioning
confidence: 99%